Harry Potter and the chamber of secrets - Rowling, J. K.; Bloomsbury Publishing (London : Bloomsbury, 1998)
When the Chamber of Secrets is opened again at the Hogswart School for Witchcraft and Wizardry, second-year student Harry Potter finds himself in danger from a dark power that has once more been released on the school.
Keywords: Hogwarts School of Witchcraft and Wizardry (Imaginary place) -- Fiction; Large print books; Magic -- Fiction; School stories; Wizards -- Fiction; England -- Fiction